2016
DOI: 10.1007/s10620-016-4178-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intragastric Balloons on Liver Enzymes: A Systematic Review and Meta-Analysis

Abstract: The use of intragastric balloon decreases liver enzymes and is potentially an effective short-term treatment for NAFLD as part of a multidisciplinary approach. Larger, more rigorous trials are needed to confirm the effect of IGBs on NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 53 publications
1
29
0
1
Order By: Relevance
“… 78 Intragastric balloons (IGB) have been shown to decrease liver enzymes and improve liver histology. 79 , 80 Histological response to IGB therapy was evaluated in a single-blinded randomized controlled trial. 80 The control arm received dietary intervention and sham endoscopy.…”
Section: The Effect Of Weight Loss and Treatment Optionsmentioning
confidence: 99%
“… 78 Intragastric balloons (IGB) have been shown to decrease liver enzymes and improve liver histology. 79 , 80 Histological response to IGB therapy was evaluated in a single-blinded randomized controlled trial. 80 The control arm received dietary intervention and sham endoscopy.…”
Section: The Effect Of Weight Loss and Treatment Optionsmentioning
confidence: 99%
“…Endoscopic insertion of the intragastric balloon (IGB) is a minimally invasive procedure leading to premature satiation, prolonged satiety, and influences the hormone levels regulating energy balance [1][2][3][4][5][6][7] The weight reductions induced by IGB are retained by a relatively low number of patients over longer periods after its removal [1,[8][9][10]. As physical activity (PA) plays an important role in promoting long-term weight maintenance [11], we have evaluated changes in PA accompanying IGB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In time, robust data supporting the use of this liquid-filled 6month indwelling balloon was created. Several meta-analyses have shown its efficacy and safety against placebo treatment [26], against diet alone [27], to treat severe obesity [28], to address obesity-related comorbidities [29] and nonalcoholic steatohepatitis [30]. Long-term data are slightly more limited, but a few studies with 5-year followup have already demonstrated some weight loss maintenance after the IGB removal [31,32].…”
Section: Liquid-filled Balloonsmentioning
confidence: 99%